In silico screening of selected natural product compounds against human neutrophil elastase - Go, Johnalyn C. (Animo Repository, 2019)
Human neutrophil elastase (HNE) is one of the key proteases present in the neutrophil and is involved in the pathogenesis of different inflammatory disorders. In recent years, the investigation for potential HNE inhibitors are increasing and one of the strategies in drug discovery is the use of in silico drug screening of the reported isolated compounds from natural products. In this study, the docking behavior of HNE with a series of compounds isolated from herbs that inhibit lung inflammation was investigated. iGEMDOCK v.2.1. (Graphical Environment for Recognizing Pharmacological Interactions and Virtual Screening) was used for the docking, virtual screening, and post-screening analysis of pharmacological interactions between the enzyme HNE and various lead compounds as the ligand. And based on the results, Compound 22 ([(2R,3R, 4S, 6S0-3,4,5- trihydroxy-6{[(2R)-5-hydroxy-2-(4-hydroxyphenyl0-4-oxo-2,3- dihydro-1-benzopyran-7-yl]oxy}oxan-2-yl]methyl(2E)-3-4- hydroxyphenyl)prop-2-enoate has the highest inhibition potential according to the calculated Gibbs free energy. The finding of this study is the first to be reported based on the current knowledge of the authors. It is recommended that further analysis of the test compound must be performed both in vitro and in vivo to validate its bioactivity.